ISSUES OF SOCIAL PROTECTION AND LABOR INVOLVEMENT OF DISABLED WORLD WAR II VICTIMS (ON THE EXAMPLE OF UZBEKISTAN) - Parnomov Alisher Bozorovich (American Journals Publishing, 2025)
This article discusses the issues of social protection and employment of disabled people of World War II using the example of Uzbekistan. It analyzes the procedures for assigning benefits by disability groups, the legal significance of the pension certificate, and forms of material assistance provided by the state. It also extensively examines the system of retraining, employment, and social benefits for disabled people. Based on practical experience in the Kashkadarya region, mechanisms for supporting disabled people and their families are highlighted. The study reveals the economic and moral significance of the system of employing disabled people in ensuring the stability of society during the war.
Keywords: World War II, disabled people of war, social protection, pension certificate, material assistance, employment, retraining courses, state policy, Kashkadarya region, social stability.